Cerebral Ischemia Induced Proteomic Alterations: Consequences for the Synapse and Organelles - Costain, Willard J.; Haqqani, Arsalan S.; Rasquinha, Ingrid; Giguere, Marie-Soleil; Slinn, Jacqueline (IntechOpen, 2012)
None